Medullary brain abscess secondary to dental procedure caused by Streptococcus intermedius - Verma, Amit (BMJ Case Rep, 2021)
Brainstem abscess is an uncommon occurrence in itself and an abscess in the medulla oblongata is even rarer. Although these abscesses have established association with head and neck infections, we report the first known case of medullary abscess that was found to be strongly associated with dental procedure. Important point to note is that a simple procedure like tooth extraction can predispose spread of infective seeding to distant sites. High clinical index of suspicion and early diagnosis are essential, as if left untreated, the brainstem abscess is almost always fatal otherwise.